The Study of Residual Chemical Carryover in Gas Well Production Facilities: A Case Problem - Purnomosidi; Indriani, Erdila; S. Putri, Lathifah; Rahalintar, Pradini; Harnada R., Restu (Scientific Contributions Oil and Gas, 2026)
The PT JM Field is capable of producing approximately 133 MMSCFD of gas and 5,600 BCPD of condensate with fluid behavior characterized by retrograde condensation such as mercury-bearing gas systems. These conditions show the importance of filtration in ensuring safe and reliable downstream operations. However, an operational issue was identified in 2024 in the form of an unusually high differential pressure which reached 30 psid across the Condensate Mercury Pre-Filter. The condition was a reflection of partial blockage at the filter outlet and led to a reduction in the system performance. Therefore, this study aimed to identify the root cause through the laboratory analysis of sludge collected during pipeline pigging between the PG and the KCR Gas Plants. The results showed that the GEOPIC sample consisted of 12.03 wt.% solid and 21.52 wt.% liquid fractions while the BIDI2 had 5.70 wt.% and 42.86 wt.% respectively. Elemental analysis also confirmed the presence of C, H, N, S, and Na while FTIR spectroscopy showed characteristic C=N, N–H, and S=O functional groups which were the reflection of a strong similarity to imidazolinamide-based corrosion inhibitors. Ionic analysis further detected Cl⁻, PO₄³⁻, and NH₄⁺ ions in the pigging fluid which were commonly associated with the corrosion inhibitors applied in the system. The results led to the implementation of several mitigation measures such as filter replacement, pipeline pigging optimization, and equipment inspection during the Turnaround (TAR). These actions successfully mitigated sludge accumulation and restored normal filtration performance.